The issue of hypotheses and scientific theories in the philosophical thoughts of Marian Smoluchowski - Dziekan, Małgorzata (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2017)
The main purpose of this paper is to investigate and reconstruct the philosophical thoughts in Marian Smoluchowski’s papers (in his publications and in unknown manuscripts as well). He was an outstanding Polish physicist, who lived at the turn of the XIX and XX century. Smoluchowski was particularly interested in theoretical physics. His achievements in this discipline, some even very significant, have caused him to be perceived mainly as a physicist. His work in the theory of fluctuations and kinetic theory of gases, especially in the theory of Brownian motions, is well known to physicists. My attention in this paper is focused on the metascientific problems which dominated his philosophical reflections. His analysis in the fields on philosophy of science (the concept of hypothesis, theory) ought to be perceived in light of physics. Philosophical reflections were at the margins of science which he practiced – physics was always the background to his deliberations. An important limit to our deliberations was set by concentrating on issues typical of the philosophy of science. In Smoluchowski’s case, however, it is difficult to say that his branch of philosophy is characterized by systematic reflection. It is difficult to classify his reflection in the framework of any given philosophical trend.